2015
DOI: 10.1111/ejh.12688
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics in multiple myeloma patients progressing into extramedullary disease

Abstract: These data show that plasma cells harbor more aberrations during their transformation into extramedullary form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 39 publications
2
35
1
1
Order By: Relevance
“…EMM at relapse and/or associated with soft tissues is more aggressive than when present at diagnosis and/or bone related. Our patient fulfilled several adverse prognosis characteristics, as the EMM was detected in a late relapse, affecting only soft tissues, that is, pericardium and pleura, and displaying chromosomal alterations related with the development of EMM, such as t (4;14), del (13)(q14), and disruption of IgH (14q32) .…”
Section: Discussionmentioning
confidence: 85%
“…EMM at relapse and/or associated with soft tissues is more aggressive than when present at diagnosis and/or bone related. Our patient fulfilled several adverse prognosis characteristics, as the EMM was detected in a late relapse, affecting only soft tissues, that is, pericardium and pleura, and displaying chromosomal alterations related with the development of EMM, such as t (4;14), del (13)(q14), and disruption of IgH (14q32) .…”
Section: Discussionmentioning
confidence: 85%
“…8 Recent advances in therapy-for instance, the introduction of thalidomide and lenalidomide as treatments for MM-may contribute to increases in the incidence of EMM. 6,8 These drugs have been shown to have antiangiogenic and immunomodulatory effects that alter the production of interleukin-6 and tumour necrosis factor-α; this in turn …”
Section: Discussionmentioning
confidence: 99%
“…Carfilzomib was given on day 1,2,8,9,15, and 16 as intravenous (IV) short infusion in a 28-day cycle. We started carfilzomib at a dose of 20 mg/m 2 on day 1 and 2 of the first cycle, and the dose was increased to 27 mg/m 2 on day 8 if tolerated.…”
Section: Treatment Response and Outcomementioning
confidence: 99%
“…C-X-C-motif chemokine receptor 4 (CXCR4) expression and hypoxia have also been reported to play a potential role in EMD growth [6,7]. Moreover, high-risk cytogenetics are significantly enriched in MM with EMD [8][9][10][11][12], and studies consistently showed EMD to be associated with poor outcome [12][13][14][15][16]. To date, there is no established approach for treatment of relapsed/refractory multiple myeloma (RRMM) with EMD.…”
Section: Introductionmentioning
confidence: 99%